The Influence of Lecturer Competence, Work Motivation, and Organizational Commitment on Leadership in Higher Education in Banyuwangi Regency - Haya Haya (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the influence of lecturer competence, work motivation, and organizational commitment on leadership in universities in Banyuwangi Regency. The research uses a quantitative approach with an explanatory method. Data was collected from permanent lecturers of universities using questionnaires and analyzed with SEM-PLS through SmartPLS 3. The results of the study showed that lecturer competence had a positive effect on leadership, work motivation had a negative effect, while organizational commitment had the greatest positive influence. The R-Square value of 0.356 indicates that all three variables explain 35.6% of the leadership variation. These findings recommend increasing organizational commitment and lecturer competencies to strengthen leadership in higher education.